The Application of Islamic Da'wah Functions in Cartoon Visual Media in Nussa Animation - Ridha, Muhammad; Rubino (Institut Agama Islam Syarifuddin Lumajang, 2023)
Da'wah Islam is a communication effort aimed at influencing individuals or societies by making them aware of and convinced of the truth of Islam, as well as by making them willing to adhere to it and deepening its teachings. With the mass media (mass communication), it is hoped that they are willing to believe that Islam will guide them to the straight and true path of Allah. Dakwah can be done face-to-face or indirectly. In order to achieve the goal of da'wah, it is necessary to adapt the language and culture or customs adopted by the community. Islamic communication is a way of communicating that is Islamic in nature and that aims to convey a message or information based on the Qur'an and hadith and has the functions of information, convincing, reminding, motivating, entertainment, socializing, and being spiritual. Cartoon media is a form of graphic communication, namely an interpretive image that uses symbols to convey a message quickly and concisely. This research is carried out descriptively and qualitatively using a pragmatic approach. Research data was collected through library research. Nussa, an animated da'wah film packaged with the goal of teaching Islamic values without boring children, is one of the domestic animated films. Nussa is an animated web series that aims to help parents and children develop morality and character. Through fun stories with Muslim themes in the foundation of Islamic animation, Nussa applies Islamic communication functions so that the Islamic messages broadcast reach the audience. Stories in Nussa animation can provide information that is easily captured by children. This information becomes motivation for the audience, and besides that, it can spark discussion among the audience. Nussa's animation entertains children because the story's contents are felt to be not too heavy, but it still provides good spiritual education due to its amusing visual appearance rather than focusing solely on the message's content Keywords: Cartoon Media, Da'wah, Nussa Animation